O imperativo do paradoxo: natureza humana, desnaturação e perfectibilidade em Rousseau - Ferreira Junior, Marcelo (Universidade Federal de São Carlos, 2024)
The aim of this study is to support an interpretation of the uniqueness of Jean-Jacques Rousseau's thought in the midst of the Enlightenment. Starting from the incompatibilities pointed out, we maintain the emergence of an ethical attitude that animates Rousseau's various writings, through which his ideas acquire a coherence, sustained by a philosophical orientation around problems that are articulated within the scope of his “theory of man”, more precisely, the paradoxical status of the conception of human nature and its inherent denaturation. In this working hypothesis, in short, the notion of perfectibility, as developed in the Discourse on Inequality, would have a paradigmatic place for understanding Rousseau's “system”.
The imperative of paradox: human nature, denaturation and perfectibility in Rousseau
Keywords: Moral; Iluminismo; Rousseau; Natureza humana; Perfectibilidade; Enlightenment; Human nature; Perfectibility; CIENCIAS HUMANAS::FILOSOFIA; CIENCIAS HUMANAS::FILOSOFIA::HISTORIA DA FILOSOFIA; CIENCIAS HUMANAS::FILOSOFIA::EPISTEMOLOGIA; CIENCIAS HUMANAS::FILOSOFIA::ETICA; CIENCIAS HUMANAS::FILOSOFIA::METAFISICA